eHealth in North America - Borycki, E. M.; Newsham, D.; Bates, D. W. (Yearbook of Medical Informatics, 2013)
Objective: The overall objective of this paper is to provide an overview of the current status of electronic health record (EHR) adoption and implementation in Canada and the United States.Methods: A review and synthesis of the empirical and grey literature about adoption of electronic health records in Canada and the United States was undertaken.Results: Both Canada and the United States have experienced increases in their adoption rates. More specifically, 2012 adoption statistics reveal that the electronic medical record adoption rate in the United States is 69% and in Canada it is 57%. Significant investment by both governments has increased adoption of electronic records across North America.Conclusions: In the United States and Canada there has been a significant rise in the adoption of electronic records by health professionals with the aid of national government incentive programs.
Keywords: Electronic health record; adoption; diffusion of innovation; national programs